A descriptive analysis on the factors of alleviating poverty among women entrepreneurs - Nik Syuhailah Nik Hussin; Nik Madeeha Nik Mohd Munir; Zuraimi Abdul Aziz; Mohd Rafi Yaacob (2015)
In the recent years, the influx of women in business continues to record poor performance in combating the poverty. Poverty is rampant and become main issue in developing countries, as it will improve the socioeconomic of the countries. The objective of this research is to find out the contributing factors in alleviating poverty for women entrepreneurship. A total of 196 samples were collected from women entrepreneurship in Terengganu and Kelantan. Data analysis was conducted using SPSS 20.0. The results indicate that the personality, cultural, environment, microfinance and entrepreneurial were the factors influenced in alleviating poverty among women entrepreneurs.